School-based mindfulness training in early adolescence: what works, for whom and how in the MYRIAD trial?. Issue 3 (12th July 2022) - Montero-Marin, Jesus; Allwood, Matthew; Ball, Susan; Crane, Catherine; De Wilde, Katherine; Hinze, Verena; Jones, Benjamin; Lord, Liz; Nuthall, Elizabeth; Raja, Anam; Taylor, Laura; Tudor, Kate; et al.
Abstract : Background: Preventing mental health problems in early adolescence is a priority. School-based mindfulness training (SBMT) is an approach with mixed evidence. Objectives: To explore for whom SBMT does/does not work and what influences outcomes. Methods: The My Resilience in Adolescence was a parallel-group, cluster randomised controlled trial (K=84 secondary schools; n=8376 students, age: 11–13) recruiting schools that provided standard social–emotional learning. Schools were randomised 1:1 to continue this provision (control/teaching as usual (TAU)), and/or to offer SBMT ('.b' (intervention)). Risk of depression, social–emotional–behavioural functioning and well-being were measured at baseline, preintervention, post intervention and 1 year follow-up. Hypothesised moderators, implementation factors and mediators were analysed using mixed effects linear regressions, instrumental variable methods and path analysis. Findings: SBMT versus TAU resulted in worse scores on risk of depression and well-being in students at risk of mental health problems both at post intervention and 1-year follow-up, but differences were small and not clinically relevant. Higher dose and reach were associated with worse social–emotional–behavioural functioning at postintervention. No implementation factors were associated with outcomes at 1-year follow-up. Pregains−postgains in mindfulness skills and executive function predicted better outcomes at 1-year follow-up, but the SBMT was unsuccessful to teach these skills with clinical relevance. SBMT as delivered in this trial is not indicated as a universal intervention. Moreover, it may be contraindicated for students with existing/emerging mental health symptoms. Clinical implications: Universal SBMT is not recommended in this format in early adolescence. Future research should explore social−emotional learning programmes adapted to the unique needs of young people.